Evaluation of diferent strains of Saccharomyces cerevisiae for ethanol production from high‑amylopectin BRS AG rice (Oryza sativa L.) - Almeida, Isabela Castro de (2022)
Ethanol is the main biofuel produced by fermentation route and the search for new feedstocks to produce fuel ethanol is still a great challenge. This work aims to compare the ethanol production from a new irrigated rice cultivar BRS AG to the conventional cultivar BRS PAMPA applied in Brazil. Six diferent commercial strains of Saccharomyces cerevisiae (BG-1, CAT-1, FT-858, JP-1, PE-2, and SA-1) were applied in fermentation reactions. Fermentations performed with BRS PAMPA rice revealed that the highest yields were achieved with strain SA-1, corresponding to 93.0% of the theoretical maximum and fnal ethanol concentration of 58.92 g L−1, and with CAT-1, a yield of 92.7% and fnal ethanol concentration of 58.93 g L−1. For the fermentations with BRS AG rice, the highest yields were obtained with strain FT-858, exhibiting a 89.6% yield and fnal ethanol concentration of 62.45 g L−1, and with CAT-1, 87.9% yield and fnal ethanol concentration of 61.25 g L−1 were achieved. The most appropriate microorganism for ethanol production using BRS PAMPA rice and BRS AG rice was CAT-1. Comparatively, the ethanol yield and productivity using BRS AG were higher than those observed for BRS PAMPA for all strains, except for PE-2 and SA-1 that led to very similar results. The experimental results showed that the giant rice BRS AG is an excellent feedstock for fuel ethanol production in lowland felds.